AN ANALYSIS OF THE FACTORS INFLUENCING THE USE OF ACCOUNTING INFORMATION SYSTEMS BASED ON E-COMMERCE IN MSMEs - Aristina, Vingki Dewi; Puspita, Erna; Kurniawan, Andy (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
Analysis of the variables influencing how MSMEs employ e-commerce-based accounting information systems. The goal of this study is to determine the effects of accounting knowledge, sales turnover, educational attainment, and business age on MSMEs' use of e-commerce-based accounting information systems. This research was conducted on MSMEs in Pare District, Kediri Regency with a total population of 588. sampling in this study used the Slovin formula, totaling 85 samples. Multi-linear regression analysis utilizing the SPSS 21 program is the analytical technique used. This research uses quantitative methods with causal study techniques. Based on the tests conducted in this study, the utilization of e-commerce-based accounting information systems is significantly influenced by Education level and business age both have an impact on sales turnover, accounting knowledge, and the adoption of e-commerce-based accounting information systems simultaneously (together), while the variables of accounting knowledge and business age sales turnover and educational level partially have no significant impact on any of these variables.